Some Issues in The Development of Professional Competencies of Music Culture Teachers - Mustafaev Bakhtiyor Ibragimovich (Indonesian Journal Publisher, 2025)
This article explores current issues related to the development of professional competencies among teachers of music culture. It analyzes the role of teachers in improving the quality of music education, highlights the importance of developing both musical and pedagogical skills, and examines innovative approaches to organizing music lessons. Special attention is given to the necessity of continuous professional development, the integration of modern educational technologies, and the cultivation of students’ aesthetic, moral, and cultural values through music education. The article also outlines the pedagogical opportunities available to teachers and stresses the need for creativity, professionalism, and a strong ethical foundation in the teaching process. By addressing these aspects, the study contributes to a deeper understanding of how the professional competence of music culture teachers can be enhanced in the context of modern educational reforms.